A Palette of Fluorescent Probes with Varying Emission Colors for Imaging Hydrogen Peroxide Signaling in Living Cells - Dickinson, Bryan C. (2010)
We present a new family of fluorescent probes with varying emission colors for selectively imaging hydrogen peroxide (H(2)O(2)) generated at physiological cell signaling levels. This structurally homologous series of fluorescein- and rhodol-based reporters relies on a chemospecific boronate-to-phenol switch to respond to H(2)O(2) over a panel of biologically relevant reactive oxygen species (ROS) with tunable excitation and emission maxima and sensitivity to endogenously produced H(2)O(2) signals, as shown by studies in RAW 264.7 macrophages during the phagocytic respiratory burst and A431 cells in response to EGF stimulation. We further demonstrate the utility of these reagents in multicolor imaging experiments by using one of the new H(2)O(2)-specific probes, Peroxy Orange 1 (PO1), in conjunction with the green-fluorescent highly reactive oxygen species (hROS) probe, APF. This dual-probe approach allows for selective discrimination between changes in H(2)O(2) and hypochlorous acid (HOCl) levels in live RAW 264.7 macrophages. Moreover, when macrophages labeled with both PO1 and APF were stimulated to induce an immune response, we discovered three distinct types of phagosomes: those that generated mainly hROS, those that produced mainly H(2)O(2), and those that possessed both types of ROS. The ability to monitor multiple ROS fluxes simultaneously using a palette of different colored fluorescent probes opens new opporunities to disentangle the complex contributions of oxidation biology to living systems by molecular imaging.